Cosmic magnetic fields - Klare, Gerhard (Reviews in modern astronomy, 1995)
Karl Schwarzschild lecture: X-rays from neutron stars / J.E. Tr(c)ơmper--Solar magnetic fields / M. Sch(c)ơssler--Ludwig Biermann Award lecture: Properties of solar magnetic fields from speckle polarimetry / Ch.U. Keller--Equilibrium and stability of quiescent prominences / D. Schmitt, U. Degenhardt--Simulation of the interaction of convective flow with magnetic elements in the solar atmosphere / O. Steiner, U. Grossmann- Doerth, M. Kn(c)œlker, M. Sch(c)ơssler--Polarization by circumstellar dust - modelling and interpretation of polarization maps / O. Fischer--Accretion and magnetism - AM Herculis stars / A.D. Schwope--White dwarfs as magnetic stars / G.D. Schmidt--Globular cluster systems of elliptical galaxies / T. Richtler--Galactic and extragalactic magnetic fields / R. Wielebinski-- Magnetic fields and the physics of active galactic nuclei / M. Camenzind--Broad emission-line variability studies of active galactic nuclei / M. Dietrich--Hot, X-ray emitting plasma, radio halos, and magnetic fields in clusters of galaxies / H. B(c)œhringer--How empty are the voids? Results of an optical survey / U. Hopp, B. Kuhn--Cosmic dynamos / K.-H. R(c)Þdler-- Three-dimensional magnetic reconnection in space- and astrophysical plasmas and its consequences for particle acceleration / M. Hesse--Condensation in gravitating systems as phase transition / M.K.-H. Kiessling